2010
DOI: 10.1007/s10096-010-0964-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of antimicrobial therapy in the intensive care unit: impact on incidence of ventilator-associated pneumonia caused by antibiotic-resistant Gram-negative bacteria

Abstract: The development of antibiotic resistance is associated with high morbidity and mortality, particularly in the intensive care unit (ICU) setting. We evaluated the effect of an antibiotic rotation programme on the incidence of ventilator-associated pneumonia (VAP) caused by antibiotic-resistant Gram-negative bacteria. We conducted a 2-year before-and-after study at two medical-surgical ICUs at two different tertiary referral hospitals. We included all mechanically ventilated patients admitted for ≥48 h who devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
(56 reference statements)
0
20
0
2
Order By: Relevance
“…Yet again, the investigation disappointingly showed beneficial effects only in a certain subgroup of bacterial population, such as fewer cases of VAP caused by P. aeruginosa (8.35 per 1,000 days of mechanical ventilation in the first period and 2.33 per 1,000 days of mechanical ventilation in the rotation period; P = 0.02). The investigators did not detect a significant difference in ICU mortality 35 . Thus, the benefit of cycling programs might be limited to specific subsets of resistant bacteria.…”
Section: Critical Analysis Of the Published Workmentioning
confidence: 91%
“…Yet again, the investigation disappointingly showed beneficial effects only in a certain subgroup of bacterial population, such as fewer cases of VAP caused by P. aeruginosa (8.35 per 1,000 days of mechanical ventilation in the first period and 2.33 per 1,000 days of mechanical ventilation in the rotation period; P = 0.02). The investigators did not detect a significant difference in ICU mortality 35 . Thus, the benefit of cycling programs might be limited to specific subsets of resistant bacteria.…”
Section: Critical Analysis Of the Published Workmentioning
confidence: 91%
“…In a two-centre Italian trial, rotation of cephalosporins, fluoroquinolones, carbapenems and piperacillin-tazobactam during 12 months was associated with a nonsignificant reduction of the incidence of VAP caused by Gram-negative bacteria, including antibiotic-resistant bacteria, without determinable effects on LOS or ICU-mortality [70]. In a two-centre Italian trial, rotation of cephalosporins, fluoroquinolones, carbapenems and piperacillin-tazobactam during 12 months was associated with a nonsignificant reduction of the incidence of VAP caused by Gram-negative bacteria, including antibiotic-resistant bacteria, without determinable effects on LOS or ICU-mortality [70].…”
Section: Infection Controlmentioning
confidence: 99%
“…The efficacy of antibiotic cycling on the recovery of antimicrobial susceptibility and patient mortality is controversial. Several trials have successfully reported a recovery of susceptibility to specific antibiotics or a reduction in detection rates of multidrug-resistant bacteria [4][9]. Moreover, some studies have shown a significant decrease in mortality as a result of the trial [4], [5].…”
Section: Introductionmentioning
confidence: 99%